2014
DOI: 10.1186/1752-1947-8-138
|View full text |Cite
|
Sign up to set email alerts
|

Chryseobacterium indologenes in a woman with acute leukemia in Senegal: a case report

Abstract: IntroductionThis report documents a rare case of Chryseobacterium indologenes urinary tract infection in Senegal. Chryseobacterium indologenes is an uncommon human pathogen reported in hospital outbreaks in Taiwan and there have been some sporadic cases reported in Europe and in the USA mainly from immune-suppressed patients.Case presentationThis case report describes a 42-year-old woman of Wolofa ethnicity who was hospitalized in our Department of Internal Medicine in a Senegalese university teaching hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
1
12
1
Order By: Relevance
“…Therefore, it was suggested that C. gleum might be less virulent than E. meningoseptica and C. indologenes . In fact, we previously reported a fatal case of urinary tract infection due to C. indologenes in a woman with acute leukemia [8]. This outcome is in contrast to the present case, where the patient survived despite an advanced state of malnutrition.…”
Section: Discussioncontrasting
confidence: 89%
“…Therefore, it was suggested that C. gleum might be less virulent than E. meningoseptica and C. indologenes . In fact, we previously reported a fatal case of urinary tract infection due to C. indologenes in a woman with acute leukemia [8]. This outcome is in contrast to the present case, where the patient survived despite an advanced state of malnutrition.…”
Section: Discussioncontrasting
confidence: 89%
“…The first clinical sample of C. indologenes was isolated in 1993 from the tracheal aspirate of a patient with ventilator-associated pneumonia [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we conclude that the toxicity of C. indologenes was very weak even for the chemotherapy patients, but was lethal for the heavily immunosuppressed patients, such as the post‐alloHSCT patients . Chen et al.…”
Section: Discussionmentioning
confidence: 70%
“…Chryseobacteria are a group of gram‐negative microbes that cause a variety of infections, usually in patients with respiratory disease or immunosuppression . In 1993, C. indologenes was first isolated from the tracheal aspirate of a patient with ventilator‐associated pneumonia . To the best of our knowledge, infections caused by C. indologenes in hematopoietic stem cell transplanted patients have been reported rarely .…”
mentioning
confidence: 99%